2018
DOI: 10.1037/pha0000194
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adverse events in clinical drug trials: Identifying amitriptyline’s placebo- and baseline-controlled side effects.

Abstract: Adverse events in clinical drug trials are often poorly assessed and reported. The absence of baseline assessment and structured symptom lists, as well as the fact that most drug trials are industry-sponsored are common sources of bias. In addition, adverse events are usually assessed in patient samples, which can bias results because of the misattribution of symptoms that are part of the illness to medication intake. We aimed to identify amitriptyline's placebo- and baseline-controlled side effects by examini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…We selected those adverse symptoms that could be expected to occur relatively quickly following acute administration of the drug and to fluctuate over the course of the experiment. We followed the recommendation of Rheker et al (26) and assessed adverse symptoms twice, before the first TAP assessment (as baseline) and after the second TAP assessment, since complaints about minor bodily symptoms are extremely common in the general population (base rates up to 80%) (27, 28) and might easily be misattributed to the nasal spray intake.…”
Section: Methodsmentioning
confidence: 99%
“…We selected those adverse symptoms that could be expected to occur relatively quickly following acute administration of the drug and to fluctuate over the course of the experiment. We followed the recommendation of Rheker et al (26) and assessed adverse symptoms twice, before the first TAP assessment (as baseline) and after the second TAP assessment, since complaints about minor bodily symptoms are extremely common in the general population (base rates up to 80%) (27, 28) and might easily be misattributed to the nasal spray intake.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, we demonstrated that amitriptyline relaxed the isolated human SV graft independently of the endothelium. In a clinical study on the determination of placebo and baseline-controlled side effects of amitriptyline, the amitriptyline group reported a high level of side effects, depending on xerostomia, dizziness and subjective blood circulation [14] . Side effects, depending on the blood circulation disorder, were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Less fatal, though serious, adverse effects strongly associated with amitriptyline include anticholinergic effects (dry mouth, slight dizziness), constipation, tachycardia, and confusion. These are most likely due to the compound’s antagonism of adrenergic, muscarinic, and histaminergic receptors, contributing to the side effects of dizziness, memory impairments, and drowsiness, respectively …”
Section: Pharmacology Adverse Effects and Dosagesmentioning
confidence: 99%